A laboratory study of chemical enhanced oil recovery (CEOR) in compartmentalized sandstone reservoir: A case study of a 2-D phase macro-model reservoir - Hamza, M.F. (Asian Research Publishing Network, 2018)
The chemical enhanced oil recovery (CEOR) in the compartmentalized sandstone reservoir (CSR) using a 2-D phase macro-model system was first reported in this work. The work investigated the effect of water flooding (brine 3.5 w/v) and anionic surfactant (AOS, 2.0 v/v) as a step forward to recover oil in the CSR. In the study, a total of 4 flooding scenarios was set for both water and AOS chemical flooding using two different sand particle; sand A (< 1 mm) and B (< 2 mm), respectively. The result indicated that pure sand B had the highest oil recovery by water flooding (80 ), followed by A:B (68 ), pure A (58 ), and B:A (49 ). However, after subsequent flooding with AOS chemical when water flooding could not further recover oil, water cut reduction and additional oil recovery (AOR) had been recorded in each case. The AOR in pure sand A was found to be 4 , with water cut reduction of 20 , while B was 2.7 (water cut 13 ), A:B was 1.5 (water cut 1 ) and B:A was 0.83 (water cut 1 ). To account for these incremental amounts due to AOS, water/oil interfacial (IFT) studies were conducted. The result shows that, AOS had significantly reduced the IFT to 11.6 Â± 3.097 mN/m. This study has demonstrated that water and subsequent chemical flooding in CSR has more effect in the homogeneous system (sand A and B) compared to the heterogeneous system (A:B and B:A). Nevertheless, approximately, more than 50 of oil in place had been displaced in all flooding scenarios. Therefore, this finding is a step forward towards understanding the EOR in the CSR systems which would be useful in the body of scientific literature to benefit researchers from both academia and oil industry. Â© 2006-2018 Asian Research Publishing Network (ARPN).